2020
DOI: 10.1007/s10694-020-00950-w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Horizontal and Vertical Barriers on Fire Development for Ventilated Façades

Abstract: Although using various innovative materials for ventilated facade systems positively contribute to the energy efficiency of buildings, the application of such materials can also pose a certain risk of fire propagation through the fac¸ade. In the last decade, medium and large-scale tests, as well as numerical analysis have been performed to assess the impact of fire barriers on fire propagation through ventilated fac¸ades. However, the number of fire barriers and their specific positions can also have an effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
2
17
0
1
Order By: Relevance
“…In the tests commissioned by MHCLG at BRE, the publicly available test reports, show notable differences between the early fire growth rates from the wooden cribs with faster fire growth occurring consistently on test wall 2. A similar effect was reported from the RISE/Zagreb tests [26,32], when run outside on days with different wind speeds. Table 2 shows significant variation in the time taken from t s for the temperature to reach 300°C at level 2.…”
Section: Effect Of Ventilation On Fire Growthsupporting
confidence: 84%
See 1 more Smart Citation
“…In the tests commissioned by MHCLG at BRE, the publicly available test reports, show notable differences between the early fire growth rates from the wooden cribs with faster fire growth occurring consistently on test wall 2. A similar effect was reported from the RISE/Zagreb tests [26,32], when run outside on days with different wind speeds. Table 2 shows significant variation in the time taken from t s for the temperature to reach 300°C at level 2.…”
Section: Effect Of Ventilation On Fire Growthsupporting
confidence: 84%
“…The UK government reports do not include air velocity data. The fourth and fifth columns of Table 2 show the time taken for the temperature to reach 300°C in the tests undertaken by RISE in Zagreb [26,32]. The test wall was located outside, with the first three tests being conducted in spring, with a wind speed between 2 m s -1 and 5 m s -1 and the last three tests in summer, with Table 2 Time to Reach 300°C in UK Government Tests [31] and in RISE Tests [26] Test number a wind speed varying between 0 m s -1 and 2 m s -1 .…”
Section: Effect Of Ventilation On Fire Growthmentioning
confidence: 99%
“…Chang and Huang (2005) have discussed about the rate of fire growth based on the exponential growth, which explains the effect of the fire growth coefficient of burning material. Accordingly, Čolić and Pečur (2020) have found that fires spread both horizontally and vertically within the building. Common reasons for horizontal fire spread are open of fire doors, breakdown of compartment walls, extinction, ventilation conditions and to balance of fuel supply.…”
Section: Behaviour Of Building Firementioning
confidence: 99%
“…Due to the sudden fire growth, it leaves the cavity barrier ineffective in most cases (Building Regulations, 2010). The use of non-combustible insulation materials especially horizontal fire barrier with 300 mm and reducing the air cavity in the cladding system can delay the fire spread effectively (McKenna et al , 2019; Peng et al , 2013; Zhou et al , 2016) (Čolić and Pečur, 2020; Chen et al , 2019a). Besides, the use of mineral wool as a non-combustible fire barrier in each storey is an effective measure that can slow down the fire spread in real-time (Xin et al , 2013; Zhou et al , 2016; Zehfuß et al , 2018; Hofmann et al , 2018).…”
Section: Challenges and Recommendationsmentioning
confidence: 99%